Two C-type lectins (ReCTL-1, ReCTL-2) from Rimicaris exoculata display broad nonself recognition spectrum with novel carbohydrate binding specificity. Issue 96 (January 2020) - Wang, Gaoyang; Lei, Yutong; Kang, Ting; Li, Zhi; Fei, Hui; Zeng, Boxin; Zhou, Peng; Wang, Chunsheng; Lv, Zhengbing; Huang, Mengmeng; Xu, Xuewei
Abstract: C-type lectins are Ca 2+ -dependent carbohydrate-binding proteins containing one or more carbohydrate-recognition domains (CRDs). C-type lectins play crucial roles in innate immunity, including nonself-recognition and pathogen elimination. In the present study, two C-type lectins (designated ReCTL-1 and ReCTL-2) were identified from the shrimp Rimicaris exoculata which dwells in deep-sea hydrothermal vents. The open reading frames of ReCTL-1 and ReCTL-2 encoded polypeptides of 171 and 166 amino acids respectively, which were both composed of a signal peptide and a single CRD. The key motifs determining the carbohydrate binding specificity of ReCTL-1 and ReCTL-2 were respectively Glu–Pro–Ala (EPA) and Gln–Pro–Asn (QPN), which were firstly discovered in R. exoculata . ReCTL-1 and ReCTL-2 displayed similar pathogen-associated molecular pattern (PAMP) binding features and they bound three PAMPs—β-glucan, lipopolysaccharide and peptidoglycan—with relatively high affinity. In addition, both could efficiently recognize and bind Gram-positive bacteria, Gram-negative bacteria and fungi. However, ReCTL-1 and ReCTL-2 exhibited different microbial agglutination activities: ReCTL-1 agglutinated Staphylococcus aureus and Saccharomyces cerevisiae, while ReCTL-2 agglutinated Micrococcus luteus, Vibrio parahaemolyticus and V. fluvialis . Both ReCTL-1 and ReCTL-2 inhibited the growth of V. fluvialis . All these results illustrated that ReCTL-1 and ReCTL-2 could function as important pattern-recognition receptors with broad nonself-recognition spectra and be involved in immune defense against invaders, but their specificities are not the same. In addition, the two ReCTLs possessed different carbohydrate binding specificities from each other and from the classical pattern: ReCTL-1 with an EPA motif bound d -galactose and l -mannose, while ReCTL-2 with a QPN motif bound d -fucose and N-acetylglucosamine. Highlights: ReCTL-1, -2 could act as PRRs to recognize, bind and eliminate specific pathogens. ReCTL-1 with EPA motif was identified to bind d -galactose and l -mannose. ReCTL-2 with QPN motif could specifically bind d -fucose and N-GlcNAc.